EVALUASI CEMARAN BAKTERI SUSU YANG DITINJAU MELALUI RANTAI DISTRIBUSI SUSU DARI PETERNAK HINGGA KUD DI KABUPATEN BOYOLALI - Lamin Arjadi; Nurwantoro Nuryantoro; Dian Wahyu Harjanti (MEDIAGRO, 2017)
This study was conducted to evaluate the milk hygiene in milk distribution chain in Boyolali Regency, Central Java Province. Parameters determined were bacterial counts, reductase time and acidity. Milk samples were taken from smallholders dairy farmers, milk collecting center (MCC), dairy cooperative (KUD). The data were analyzed by paired T-Test. The result showed the bacterial counts in milk collected from farmers 6,588,625 CFU/ml, MCC 9,230,625 CFU/ml, and KUD 13,209,375 CFU/ml were all above the SNI (max 1,000,000 CFU/ml). The reductase time of milk collected from farmers, MCC and KUD were 5,9 ; 5,8 ; 5,7 hour respectively. Moreover this research found positive result in alcohol test with some milk samples collected from farmers 2 samples (12,5%) and MCC 1 sample (6,25%). In conclusion, the result indicated that the milk hygiene in Boyolali regency still need to be improve to ensure the milk safety. Keywords: milk, bacterial contamination, distribution chain.